The Effectiveness of the Resolution of Non-Performing Financing at BSI KC Palangka Raya Diponegoro Through Small Claim Court - Maimunah, Nurul Ayatul; Muhammad Zainal Arifin; Fadiah Adlina (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
This research is motivated by the existence of non-performing financing at Bank Syariah Indonesia and previous research which explained various factors that cause non-performing financing and settlement carried out by Islamic Banking, especially Bank Syariah Indonesia. In particular, this study examines the handling of non-performing financing through a small claim court at BSI KC Palangka Raya Diponegoro. This study aims to identify the factors that cause non-performing financing in BSI KC Palangka Raya Diponegoro and identify the process of resolving non-performing financing through the Small Claim Court mechanism. In addition, by reviewing the Small Claim Court process, it is hoped that insight will be gained regarding the efficiency and effectiveness of using this method. The method used in this study is descriptive analysis by collecting data through observation, in-depth interviews and documentation. The results of the study show that the non-performing financing factor at BSI KC Palangka Raya Diponegoro is dominated by a lack of attention and a sense of responsibility from customers and supported by a lack of understanding in managing finances. The handling of non-performing financing at BSI KC Palangka Raya Diponegoro implements the settlement of the non-litigation and litigation routes. Decision-making using settlement with a small claim court is based on the client's character, the existence of psychological effects and efficient time and costs. Therefore, the importance of formulating an effective non-performing financing settlement policy and small claim court as an alternative to dispute resolution in Islamic banking can be a strategic consideration for BSI KC Palangka Raya Diponegoro to overcome non-performing financing.